Influence Financial Technology, E-Commerce Adoption, and Entrepreneurial Skills on Financial Performance MSMEs With Financial Literacy and Trust As Variables Mediation Studies Cases in North Sulawesi MSMEs: Indonesia - Wendiaputra Paputungan; Yoyo Sudaryo; Nunung Ayu Sofiati; Andre Suryaningprang; Riyandi Nur Sumawidjaja (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The present investigation seeks to analyze the impact of financial technology, e-commerce adoption, and entrepreneurial capability on the financial performance of Micro, Small, and Medium Enterprises (MSMEs) in North Sulawesi Province, considering both direct effects and indirect effects mediated by financial literacy and trust. A quantitative methodology characterized by a causal research design was utilized, employing a cross-sectional survey approach with a sample of 400 MSME participants selected via purposive sampling. The data were subjected to analysis through descriptive statistics and Partial Least Squares-Structural Equation Modeling (PLS-SEM), facilitated by the SmartPLS 4 software. The results demonstrate that financial technology, e- commerce adoption, and entrepreneurial competencies exert a positive and statistically significant direct influence on MSME financial performance, with financial technology identified as the most influential predictor. Additionally, financial literacy and trust were found to significantly mediate the associations between these three independent variables and MSME financial outcomes. The proposed model accounts for 60.3% of the variance observed in MSME financial performance. These findings highlight the critical necessity of enhancing fintech and e-commerce adoption, alongside fostering improvements in financial literacy and the trust of MSME actors in digital platforms, to maximize financial performance.